Impacts of change management practices on construction project performance in Bauchi State, Nigeria - Mohammed Mukhtar Musa; Abdussamad Ibrahim Birma; Ibrahim Inuwa Ibrahim (Journal of Construction Project Management and Innovation)
Changes in construction projects are inevitable. As a result of changes, construction projects experience time and cost overruns, as well as non-conformance to set quality standards leading to poor performance. Despite several studies that have been conducted on project change management systems, not enough has been done to determine its impacts on project performance. The aim of this study is to assess the impacts of change management practices on the performance of construction projects in Bauchi State, Nigeria, with a view to improving construction project delivery in the area. The study opted for an explanatory research design. A questionnaire survey was conducted in which 190 questionnaires were administered to construction professionals using the purposive sampling technique. One hundred and forty-seven (147) were returned completed representing a 77% response rate. The data obtained were analysed by means of descriptive statistics, factor analysis and multiple regression analysis. Findings from the survey revealed that the extent of Change Management (CM) practices in the construction project in the study area was low. In addition, the impacts of CM practices on time and cost performance as well as on end users’ satisfaction was positive and significant. Similarly, its impacts on the overall project performance were also positive and significant. The CM activities identified in this study can serve as a framework for effective CMS that can be used by construction professionals in managing changes at project level.